Comparison study of advances oxidation process (aop’s) techniques in the degradation of azo dye / Nor Syaidatul Syafiqah Mohd Rashid - Mohd Rashid, Nor Syaidatul Syafiqah (Faculty of Applied Sciences, 2017)
Waste water treatment is the major problems faced by textile industry as they produce large volumes of wastewater during dyeing and finishing process. This problem give potential impact to human health hazard and a threat to aquatic life. Advanced Oxidation Process (AOP) have been studied and chosen in this study consists of combination of H2O2/UV. Photocatalytic activity of Cu2+/H2O2/UV on degradation of Congo Red (CR) dye and the optimum condition of degradation process based on different experiment conditions which are the concentration of CR used, the concentration of hydrogen peroxide (H2O2), the concentration of CuSO4 as catalyst in Fenton reagent, the pH value of CuSO4, the mass of TiO2 and the pH value of TiO2 mass were studied. Besides, the degradation efficiency of CR dye using Fenton reagent and TiO2 was compared. The result indicated that the photodegradation of CR solution are more effective in Fenton reagent process than TiO2 at pH 3. The result showed for degradation of CR solution in Fenton reagent was 99.32 % and for H2O2 concentration was at 77.16 %. As for the TiO2, the result showed less efficiency of degradation of CR dye solution than Fenton reagent. The higher percentage degradation of CR dye was at 0.32 g of TiO2 dose and at pH 3. Lastly, the effective methods for pollutant removal was in Fenton reagent due to the addition of the catalyst CuSO4,where the Cu2+ ion will undergo reduction under the ultraviolet (UV) lamp and through the photolysis of the H2O2 itself. Study found that Fenton process at optimum condition concentration CuSO4 was the best.